Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12882-016-0377-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatal outcomes among patients on maintenance haemodialysis in sub-Saharan Africa: a 10-year audit from the Douala General Hospital in Cameroon

Abstract: BackgroundEnd-Stage Renal disease (ESRD) is associated with increased morbidity and mortality. We assessed the occurrence, time-trend and determinants of fatal outcomes of haemodialysis-treated ESRD patients over a 10-year period in a major referral hospital in Cameroon.MethodsMedical records of ESRD patients who started chronic haemodialysis at the Douala General Hospital between 2002 and 2012 were reviewed. Baseline characteristics and fatal outcomes on dialysis were recorded. Accelerated-failure time and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Despite the benefit of early referral on CKD progression, the rate of late referral of patients to the nephrologist is extremely high in SSA [24,25], where access to RRT is limited [26]. Patients with CKD therefore face the problems of high out-of-pocket payment and poor outcome on RRT [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the benefit of early referral on CKD progression, the rate of late referral of patients to the nephrologist is extremely high in SSA [24,25], where access to RRT is limited [26]. Patients with CKD therefore face the problems of high out-of-pocket payment and poor outcome on RRT [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the baseline profile of patients with CKD at referral and in SSA [23,24,28,29]. Little is known on the evolution of their kidney function, related risk factors and markers of CKD progression under nephrological care.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been a leading cause of morbidity and mortality worldwide, afflicting approximately 8-16% of the global population (Jha et al, 2013) and ranking eighth among the leading causes of death. It has also been acknowledged as a troublesome disorder causing a myriad of health-related problems (Lowney et al, 2015), financial burden (Bavanandan, Ahmad, Teo, Chen, & Liu, 2016) and poor survival outcomes (Halle, Ashuntantang, Kaze, Takongue, & Kengne, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Over a quarter of patients starting hemodialysis die within the rst year with about half within the rst 6 months and those with co-existing hypertension and diabetes mellitus conveyed the poorest prognosis. Late presentation of CKD and affordability are were cited as major drivers of high early mortality [39]. The prevalence of CKD reported by studies with a single time-point assessment of kidney function or damage is likely to lead to errors in estimating of the true value.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of CKD in Cameroon ranged between 26.8% and 58.0% during a period of 1 to 10 years of follow up, Table 6 [39,48,49]. An audit of 661 medical records reported a 10-year mortality rate of 44.9% [39].…”
Section: Mortality Of Ckd In Cameroonmentioning
confidence: 99%